Public Support for Biodiversity After a Zoo Visit: Environmental Concern, Conservation Knowledge, and Self‐Efficacy. (January 2017) - Clayton, Susan; Prévot, Anne‐Caroline; Germain, Laurent; Saint‐Jalme, Michel
Abstract: The biodiversity crisis is not salient to many people. A zoo visit not only provides the opportunity to learn about the issue, but also provides direct experiences with animals that may increase public engagement. The present study used a nonequivalent pretest–posttest design to assess the impact of a zoo visit on conservation knowledge and engagement by comparing 88 visitors entering a zoo in Paris and 84 visitors on their way out. Those who had completed their visit scored higher on conservation knowledge, general concern about threats to biodiversity, and perceived self‐efficacy to protect biodiversity. Notably, conservation knowledge was not highly correlated with the other dependent variables, but self‐efficacy was significantly correlated with environmental concern, behaviour, and behavioural intent. We conclude that a zoo visit does have a positive impact on knowledge and concern, and by affecting self‐efficacy, it has the potential to influence future behavior.